ANALISIS PERAN GURU DALAM MENINGKATKAN PERKEMBANGAN SOSIAL-EMOSIONAL SISWA SD KELAS 1 - Qomariyah, Titik Nur; Daroe Iswatingsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The problem raised in this study is how the role of puru in improving the social-emotional development of MI Muhammadiyah 5 Jombang class 1 students during learning, outside learning. This study aims to describe the Role of Teachers in improving the social-emotional development of MI Muhammadiyah 5 Jombang class 1 students in the learning process and outside learning. This study uses a descriptive qualitative method. The data obtained in the study were through observation, interviews and documentation. The objects of this study were students of class 1 MI Muhammadiyah 5 Jombang and teachers or homeroom teachers in class 1. The results of the analysis of the social-emotional development of MI Muhammadiyah 5 Jombang class one students, namely first, in the learning that has been achieved, including lower class students can show involvement behavior in learning, attitudes willing to share, communicate with good language and interact with their classmates, can place themselves in study groups, show self-confidence. Second, outside of the learning that has been achieved, namely having a sense of empathy, students have the initiative to do good, students show behavior in helping fellow friends when other friends need help, do not force their own will, can solve problems when playing with friends, are able to process their own emotions when playing, build good relationships with friends. The third role of teachers in developing students' social-emotional is to foster good social-emotional development interactions inside and outside the classroom towards students, provide examples of good attitudes and words as figures to be emulated, provide stimulation in the form of guidance, to encourage the achievement of social-emotional development